Five recurring problems in international arbitration: The relationship between courts and arbitral tribunals - NG, Iris (Institutional Knowledge at Singapore Management University, 2020)
In recent years, five recurring problems regarding the relationship between courts and tribunals have gained prominence due to case law developments. These run the gamut from preliminary issues with the arbitration agreement to disputes at the enforcement stage. This article examines these problems in detail, with a view to shed new light on the question of what it means for a jurisdiction to be “pro-arbitration”. The authors argue that the oft-repeated binary categorisation of “pro-arbitration” and “anti-arbitration” jurisdictions is too broad-brush. Instead, there is no easy answer to what constitutes a truly “pro-arbitration” approach, and no one-size-fits-all approach to being a “pro-arbitration” jurisdiction.